2016
DOI: 10.1016/j.ijsu.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Six-year follow-up of patients treated with oncoplastic reduction mammoplasty: A cohort study

Abstract: Based on these long-term follow-up data, ORM is an oncologically safe treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…This study has shown that oncoplastic breast conservation is likely to offer better outcomes than mastectomy with or without breast reconstruction for many women and, together with emerging evidence to support the long‐term oncological safety of oncoplastic breast conservation, adds further support to the use of TM as an alternative to mastectomy. Further work is now needed determine whether TM improves patient‐reported outcomes and is cost‐effective compared with mastectomy with and without immediate breast reconstruction before definitive recommendations for best practice can be made.…”
Section: Discussionmentioning
confidence: 70%
“…This study has shown that oncoplastic breast conservation is likely to offer better outcomes than mastectomy with or without breast reconstruction for many women and, together with emerging evidence to support the long‐term oncological safety of oncoplastic breast conservation, adds further support to the use of TM as an alternative to mastectomy. Further work is now needed determine whether TM improves patient‐reported outcomes and is cost‐effective compared with mastectomy with and without immediate breast reconstruction before definitive recommendations for best practice can be made.…”
Section: Discussionmentioning
confidence: 70%
“…However, our study did not include patients who required completion mastectomy after failed OBC. Previous studies from our unit indicated a completion mastectomy rate between 0 -13.2% of patients treated with OBC indicating a relatively high completion mastectomy rate after initially failed OBC 8,9,14,36,37 . Although these figures cannot be projected to the practice of the whole country, it is conceivable that true incomplete margin rate after OBC is somewhat higher in Scotland.…”
Section: Discussionmentioning
confidence: 75%
“…Current evidence is largely based on single-institution retrospective series [3][4][5][6][7][8][9][10][11][12][13][14][15] . Systematic literature reviews, meta-analyses and reviews further strengthen the evidence base but numbers in many series are small 2, [16][17][18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…This study was designed and reported in line with STROBE criteria. 20 Methods for data collection in our centers have previously been described. [21][22][23][24] The research was conducted in accordance with the principles of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%